Escaping the comfort zone: A three-level perspective on filtering effects and counter-measures - Tim Schneegans (OrdnungsPolitisches Portal (OPO), 2019)
Together with the growing connectedness in the progress of globalization, researchers warn about the rise of so-called "filter bubbles" and "echo-chambers" that segregate citizens into comfort zones of self-confirming information and opinions. Regarding the Brexit referendum in 2016, DiFranzo and Gloria-Garcia (2017) blamed social media (e.g. Facebook) for trapping their users in an environment of self-confirming opinions that keeps them away from the political discourse. Besides technological filters, Geschke, Lorenz, and Holtz (2018) regard the mechanisms of filter bubbles on three levels, including technological recommender algorithms, homogeneous social networks, and individual biases. In this essay, I will follow this framework and describe certain filtering effects and deduce contraindications on all three levels. Amongst others, the concepts of social self-categorization (Tajfel, 1974), homogeneous networks (e.g. Bakshy et al., 2015), and self-confirmation biases (see the review from Garrett, 2009) might help un-derstanding filter bubbles. In order to promote public information exchange, we should not only modify filter algorithms but also become aware of our social comfort zone and our cognitive ability to select self-confirming information. Segregated groups must re-define their social identity and enlarge its definition to connect to seems-like-alien people (Pettigrew, 1998; Tajfel, 1974). This way we can promote the intrinsic human drive for curiosity as a counterweight against segregation.
Keywords: 330; echo chamber; filter bubble; digital citizenship; political psychology